COMPARATIVE ANALYSIS OF ISOMETRIC STRENGTH AND RANGE OF MOTION OF SHOULDER, BEFORE AND AFTER A SINGLE BADMINTON MATCH IN YOUNG ELITE BADMINTON PLAYERS - Mamoona Tasleem Afzal; Muhammad Shakir Khan; Anas Bin Mujeed; Asaad Saleem; Maryam Aslam; Sairish Sairien (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: This study investigates the impact of a single badminton match on shoulder ranges of motion (ROM) and isometric strength in young elite badminton players from Rawalpindi/Islamabad. Shoulder function is crucial in badminton, yet the acute effects of match play remains under explored. Objective: The primary objective is to assess changes in shoulder adduction ROM, ROM across various movement planes, and isometric strength before and after a single badminton match. The study aims to contribute valuable insights into the dynamic aspects of shoulder function in response to acute sport-specific demands. Methodology: A comparative cross-sectional study was conducted at Islamabad Sports Complex consisting of 56 participants meeting the inclusion criteria Participants include young elite badminton players, and assessments encompassed shoulder adduction ROM, ROM in flexion, extension, abduction, internal rotation (IR), and external rotation (ER), and isometric strength of specific muscle groups before and after a single badminton match. Statistical analyses employed paired t-tests, Wilcoxon Signed Rank Tests, and descriptive statistics using SPSS 23. Results: While shoulder adduction ROM and isometric strength did not exhibit significant changes post-match, significant decreases were observed in flexion (p = 0.04*) and abduction (p = 0.04*) ROM. Conversely, extension, IR, and ER did not show significant differences (p = 0.11, 0.78, and 0.09, respectively). Conclusion: It was concluded that a single badminton match may selectively impact certain shoulder ranges of motion, emphasizing the importance of assessing different movement planes. However, shoulder adduction ROM and isometric strength remained relatively stable.